2020
DOI: 10.3892/ijmm.2020.4581
|View full text |Cite|
|
Sign up to set email alerts
|

Long non‑coding RNA PRNCR1 exerts oncogenic effects in�tongue squamous cell carcinoma in�vitro and in�vivo by sponging microRNA‑944 and thereby increasing HOXB5�expression

Abstract: A long non-coding RNA (lncRNA) called prostate cancer-associated non-coding RNA 1 (PRNCR1) serves crucial roles in the aggressive phenotypes of colorectal cancer and non-small cell lung cancer. However, there is little research on the expression profile, clinical value and detailed functions of PRNCR1 in tongue squamous cell carcinoma (TScc). The aim of the present study was to determine PRNCR1 expression in TScc and to examine the involvement of PRNCR1 in TScc progression. The molecular mechanisms behind the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 48 publications
(49 reference statements)
0
13
0
Order By: Relevance
“…Knockdown of TUG1 suppressed cisplatin resistance to CAL27/CDDP and SCC25/CDDP cells via modulating CXCR4 and miR‐133b. Lin et al 36 noted that PRNCR1 played as one oncogenic lncRNA gene in the development of TSCC via regulating HOXB5/ miR‑944. Yan et al 37 suggested that knockdown of PCAT‐1 suppressed metastasis of proliferation of TSCC cell through up‐regulating P21.…”
Section: Discussionmentioning
confidence: 99%
“…Knockdown of TUG1 suppressed cisplatin resistance to CAL27/CDDP and SCC25/CDDP cells via modulating CXCR4 and miR‐133b. Lin et al 36 noted that PRNCR1 played as one oncogenic lncRNA gene in the development of TSCC via regulating HOXB5/ miR‑944. Yan et al 37 suggested that knockdown of PCAT‐1 suppressed metastasis of proliferation of TSCC cell through up‐regulating P21.…”
Section: Discussionmentioning
confidence: 99%
“…miR-326 (sponging) i. HOXB5 over-expression ii. FSCN-1 over-expression Prognostic Lin et al ( 2020 ); Liu et al ( 2021 ) Colorectal cancer Over expression Proliferation (↑) Migration (–) Invasion (–) apoptosis (–) N/A N/A Diagnostic Prognostic Yang et al ( 2016 ) NSCLC non-small cell lung carcinoma; OSSCC oral squamous cell carcinoma; EMT epithelial-to-mesenchymal transition ↑: positive impact; ↓: negative impact; –: no effect; N/A: data not available
Fig. 3 Summarized information on functional mechanism of PRNCR1 in oncogenesis.
…”
Section: Introductionmentioning
confidence: 99%
“…In oral squamous cell carcinoma (OSCC) and tongue squamous cell carcinoma (TSCC), the most common type of OSCC, PRNCR1 over-expression was reported in primary tumors as well as in cancer cell lines (Liu et al 2021 ; Lin et al 2020 ). Following PRNCR1 knockdown reduced tumor phenotypes of cancer cells like proliferation, migration, and invasion suggested the association of the lncRNA in disease pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations